MELACAK KELEMAHAN : MENGAPA PENGIMPLEMENTASIAN KEBIJAKAN UJI EMISI DI DKI JAKARTA TAK EFEKTIF? - Alvino Aryasena; Arya Pratama Iqbal; Raditya Rahman Kusuma (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
The DKI Jakarta government took proactive measures to address the increasing air pollution in Jakarta by implementing an emission test policy. However, in reality the emission test policy did not work properly due to several problems, and the emission test tickets were also dismissed after one day from the start date. This paper discusses the reasons for the failure of the emission test policy in Jakarta from two main perspectives: the public and the government. To support the analysis of this issue, this paper uses library research as the method of writing. The result found that many parties consider this policy ineffective in its implementation. The public sees the failure of this policy as a result of infrastructure deficiencies and lack of socialization. In addition, the high cost of emission testing is a challenge for some people. The failure of the emission test policy is also a concern for the government, as the lack of law enforcement is one of the main problems. Many vehicles that should not qualify for emission testing continue to drive on the road without being sanctioned. This gives the impression that policy implementation is ineffective and inconsistent.